Operating experience with nuclear power statio ns in member states in 2007 (Vienna, Austria : International Atomic Energy Agency, 2006)
Contains a historial summary of performance and outages during the l ifetime of individual plants and figures illustrating worlwide performa nce and statistical data.
This report is the thirty-eighth in the Agency's series of annual re ports on operating experience with nuclear power stations in Member Sta tes
Produced by the IAEA in Austria
Keywords: Nuclear reactors; Nuclear power plants -- Reporting